Caracterización de las pasturas para maximizar producción animal - Lascano Aguilar, Carlos Eduardo (2002)
This paper discusses strategies to overcome biotic and abiotic constraints and improve forage quality in grasses using conventional breeding methods. Factors that should be considered to ensure success in improvement programs are outlined. The benefits that can be achieved in animal production through the development of grass cultivars with high digestibility are discussed. In addition, the paper summarizes factors related to protein and carbohydrate utilization by ruminants, the opportunities that biotechnology offers to change the composition of forages, and how these changes can improve the efficiency of utilization of nutrients by rumen microbes and by the host animal. With the evidence reviewed it was concluded that significant opportunities exist in the short run to introduce resistance to pests and diseases and improve digestibility in tropical and temperate grasses through the use of conventional breeding schemes. Options such as NIRS and molecular markers could be used to accelerate and achieve cost efficiency in conventional breeding programs. In the medium term, there is the option of improving forage species through the introduction of genes coding for quality attributes (i.e. more soluble carbohydrates, interference with lignin production and production of plant proteins with different degradability) or for resistance to biotic (pests) and abiotic (tolerance to high soil Al) factors.